IMPACT OF RAIN-FED RICE CROPPING SYSTEMS ON SOIL FERTILITY IN CENTRAL AND NORTHERN BENIN (1) - Anago, Firmin N; DAGBENONBAKIN, Gustave D.; AGBANGBA, Codjo Emile; Oussou, Brice; CHABI, Faki; SAIDOU, ALIOU; AMADJI, LUCIEN GUILLAUME (My University, 2020)
Benin has tremendous asset for rice production. However, nationwide, rice production is characterized by a low level of productivity due to inadequate agricultural practices. In order to evaluate the effect of the rain-fed rice cropping systems on soil fertility in northern and central Benin, 362 rain-fed rice farmers were surveyed in the municipality of Banikoara, Kandi, Ouèssè and Glazoué in Benin. Soil samples were taken from the rice fields and analyzed at laboratory for the determination of physicochemical parameters. Three main rain-fed rice cropping systems were identified. In northern Benin, two cropping systems predominated. The system 1 was characterized by no use of fertilizers and use of crop residues as animal feed while in the system 2 less than 100 kg/ha of fertilizers was used and crop residues were also used as animal feed. The predominant cropping system in central Benin, was characterized by use of 100 and 200 kg/ha of fertilizers and crop residues were left in the fields (system 3). The soils of the system 1 had a very low fertility with low organic carbon (0.19 ± 0.12%), low available phosphorus (7.17 ± 3.56 mg/kg) and low potassium exchangeable (0.13 ± 0.10 cmol/kg). The soils of the system 3 which showed low, medium and good fertility in some places with higher average organic carbon (0.88 ± 0.25%), higher available phosphorus (13.03 ± 6.63 mg/kg) and higher potassium exchangeable (0.24 ± 0.08 cmol/kg). The average rice cropped per farmer was around 2 ha in central Benin and less than 1 ha in northern Benin. Farmers’ management of soil fertility didn’t take account soil specifics conditions and suitable production. To improve the productivity of the cropping systems, it is necessary to determine the optimal doses of fertilizer and incorporate crop residues into the soil to ensure sustainable rice production.
Keywords: rice productivity; animal feed; crop residues; declining of soil fertility